Pengeringan Gambir Menggunakan Oven Pengering Suhu Terkontrol dengan Pemanas Ganda - Siregar, Batumahadi; Arfah, Mahrani; Ingtias, Fatma Tresno; Nurdiana, Nurdiana (CV. IRA PUBLISHING, 2024)
The traditional drying process of gambier using direct sunlight requires up to 4 days, or smoking methods to reduce the moisture content from 45–50% to 18–20%. However, during the rainy season, this process may take up to 7 days and often results in poor-quality gambier due to mold growth. A controlled-temperature drying process is expected to produce evenly dried gambier, shorten drying time, and achieve a moisture content of less than 14%, with a yellowish-brown color meeting the SNI 01-3391-2000 standard. A dual-heater drying oven with temperature control ensures even heat distribution across all racks. The test results showed that at a temperature of 100–115 °C, with 10 kg per rack for five racks over 4 hours, the moisture content could be reduced to below 14%, with a drying rate of 0.94 gr/s and energy consumption of 0.5 kWh. At 110 °C for 4 hours, the oven produced evenly dried gambier, met SNI standards and exhibited a yellowish-brown color. The stove is also effective during the rainy season or nighttime, supporting partners in improving the quality of gambier drying and increasing income.